A theory of Crowdfunding: A mechanism design approach with demand uncertainty and moral hazard - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
Crowdfunding provides the innovation that, before the investment, entrepreneurs contract with consumers. Under demand uncertainty, this improves a screening for valuable projects. Entrepreneurial moral hazard threatens this benefit. Focusing on the trade-off between value screening and moral hazard, the paper characterizes optimal mechanisms. Current crowdfunding schemes reflect their salient features. Efficiency is sustainable only if returns exceed investment costs by a margin reflecting the degree of moral hazard. Constrained efficient mechanisms exhibit underinvestment. Crowdfunding blurs the distinction between finance and marketing, but complements rather than substitutes traditional entrepreneurial financing. As a screening tool for valuable projects, crowdfunding unambiguously promotes social welfare.
Keywords: K12; K42; C91; D64; 330; Crowdfunding; finance; marketing; demand uncertainty; moral hazard